(untitled) (Training and Practice : Journal of Educational Sciences, 2007)
The first part of the paper gives a short overview of the situation and problems of teaching and improving reading comprehension in Hungary, regarding research and practice as well as results of reading comprehension surveys that have been stagnating on low level since decades. There is not much research in our country and there are only a few topics involved. Foreign countries’ research-results arrived late and their reception and implementation are insufficient. The professional discussions have been about initial reading teaching for a long time, improving reading comprehension has only recently become in focus. The next part of the paper reviews the most important prerequisites of improving reading comprehension based on American research touching upon both characteristics of each factors in Hungary and supposed reasons of Hungarian student’s low achievement. The main reasons -among others - according to the author are the traditional frontal teaching, the lack of student centred cooperative methods and differential teaching. Teachers use only one book, neglect motivating children to read. Pupils do not have enough reading-exercises in school, teachers cannot help readers struggling with difficulties. The author writes more in details about reading comprehension strategies and possible ways of teaching them, given that this is a fairly little known area in this country, even though in the States it has been a research topic for the past thirty years. Finally she makes some proposals to change the present unfavourable situation.